Obesity and lack of breastfeeding: a perfect storm to augment risk of breast cancer? - Ormiston, Kate; Kulkarni, Anagh; Sarathy, Gautam; Alsammerai, Sara; Shankar, Eswar; Majumder, Sarmila; Stanford, Kristin I.; Ganju, Ramesh K.; Ramaswamy, Bhuvaneswari (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) is one of the most aggressive subtypes of breast cancer with higher rates of recurrence and distant metastasis, as well as decreased 5-year survival rates. Racial disparities are evident in the incidence and mortality rates of triple negative breast cancer particularly increased in young African American women. Concurrently, young African American women have multiple risk factors for TNBC including higher rates of premenopausal abdominal obesity (higher waist-hip ratio) and lower rates of breastfeeding with higher parity, implicating these factors as potentially contributors to poor outcomes. By understanding the mechanisms of how premenopausal obesity and lack of breastfeeding may be associated with increased risk of triple negative breast cancer, we can determine the best strategies for intervention and awareness to improve outcomes in TNBC.